SEROPREVALENCE OF PESTE DES PETITS RUMINANTS (PPR) VIRUS IN GOATS, SHEEP AND CATTLE AT LIVESTOCK PRODUCTION RESEARCH INSTITUTE BAHADURNAGAR OKARA - A. Rashid; M. Asim; A. Hussain (Journal of Animal and Plant Sciences, 2008)
Peste des Petits ruminants (PPR) is a contagious viral disease of goats and sheep, characterized by pyrexia, occulo-nasal discharge, stomatitis, pneumonia and diarrohea. The disease is endemic in many regions of world and responsible for significant economic losses in goats and sheep due to high morbidity and mortality rates. In present study, 240 sera were collected from goats, sheep and cattle kept at Livestock Production Research Institute, Bahadurnagar, Okara. Competitive Enzyme Linked ImmunoSorbent Assay (c-ELISA) was used to detect the antibodies in sera against PPR virus. It was found that there was high seroprevalence of PPR antibodies in goats than other animals. The overall PPR antibody seroprevalence recorded in goats, sheep and cattle was 82.72%, 28.75% and 8% respectively.
Keywords: Peste des Petits ruminants; (PPR); Competitive Enzyme Linked Immuno Sorbent Assay (c-ELISA)